Prevalência de vírus adeno-associado (AAV) e de coinfecção com papilomavírus humano (HPV) em espécime cervical de mulheres soropositivas e soronegativas para HIV - Freitas, Luciana Bueno de (2009)
AAV is a parvovirus which depends of a helper virus to develop productive infection. Until now, there are twelve species described, which AAV2, AAV3, AAV5 e AAV9 were described infecting human beings. In the genital tract, the HPV has been the mostly related in association with AAV. A bidirectional interaction between these viruses has been described, which genes of AAV restrain the expression of HPV genes, what could reflect a protector role of AAV on the development of HPV-induced cervical carcinoma. HIV infection seems to increase the persistence and susceptibility to the HPV infection, enhancing the probability to cervical tumors. At the moment, there are no reports about AAV prevalence in patients with HIV infection. This study aimed to investigate the prevalence of AAV and the AAV-HPV coinfection in cervical secretion from HIV seropositive and seronegative women attending at the Reference Center of Sexually Transmitted Disease/AIDS, Vitória-ES. A structured questionnaire was performed to obtain sociodemographic data of all women. Cytological exams were performed and DNA was extracted using the QIAamp® DNA Mini Kit (QIAGEN), as manufacter s instructions. AAV and HPV were investigated by PCR. AAV typing was done by PCR and RFLP. AAV total prevalence was 19.7% (56/284), with 18.7% (21/112) and 20.3% (35/172) in HIV seropositive and seronegative women, respectively. AAV was detected in 27% of HPV-positive women (36/133) and in 13% of the HPV-negative women (20/151), statically significant (p=0.003). The single type detected was AAV2. Cervical findings were: 222 normal cytology, 41 inflammatory alterations, 10 atypical squamous cells of undetermined significance (ASCUS) and 11 cervical intraepithelial neoplasia class 1 and 2 (CIN 1/ 2). The women AAV-HPV-coinfected showed a lesser chance on the development of ASCUS and CIN, compared with those infected only by HPV. The highest prevalence of the AAV2 type is in accordance with other studies, which demonstrate the AAV2 as the most common in human samples. The significant association observed between AAV and HPVinfected women could suggest helper activity of HPV and corroborate previous studies. The presence of AAV reduced the chance of cervical lesions HPV-induced. Moreover, this is the first report concerning AAV prevalence in HIV-infected women and indicates that this infection does not influence the prevalences of AAV or AAV-HPV coinfection